The Griquas of Griqualand East until about 1878 - Knoll, Thelma J N (Department of Historical Studies, 2016)
I have attempted to write a history of that section of the Griqua people who from 1862 to 1872 lived as an independent nation - the word is their own - in the present Griqualand East. It has not been an easy task, and I am afraid I have not given as clear an account as I should have liked to do. The Rev. William Dower, a London Missionary Society Minister, who lived among the Griquas in Griqualand East for several years, is the only man who has written anything like a history of these people. His book I have used mainly to get an idea of the character of the Griquas and of their social condition while Dower lived with them. For the facts of their history in Griqualand East I had to go to blue books, and to unpublished material in the Archives in Cape Town. I have not had the time to go through all the material on the subject - both in the blue books and in the Archives there is a great deal which I have not touched. In view of the many contradictory statements contained in the blue books which I had at my disposal, it was indeed difficult (due perhaps to some extent to my lack of experience of official reports) to select the correct data. For the history of the Griquas before 1860 I am mainly indebted to Sir George Cory who gives a connected account of a period about which there is very little material.